Monitorización de biomarcadores sanguíneos en jugadores profesionales de fútbol durante la fase preparatoria y competitiva - Vilamitjana, J.; Vaccari, J. C.; Toedtli, M.; Navone, D.; Rodriguez-Buteler, J. M.; Verde, P. E.; Calleja-Gonzalez, J. (Revista Internacional de Ciencias del Deporte, 2017)
The aim of this study is to analyze changes of stress-related biochemical markers in Argentine professional soccer players (n = 22) at 3 timepoints during the soccer season: beginning of preseason (E1), beginning of season (E2), and after 6 weeks of competitive season (E3). The sample of players was divided in two groups of 11: starters players during the first seven matches of the season, and substitute players. Concentrations of creatine kinase (CK), lactic-acid dehydrogenase (LDH), testosterone (TL) and cortisol (C) were assayed in serum samples, and testosterone-cortisol ratio (T/C) was also calculated. We observed no significant differences between both groups during preseason (E1-E2), but a higher in-season level of TL and T/C (E3>E2; p< 0.05) was observed in non-starter players. Besides, a decrement of LDH values were determined in this group during the season (E3<E2; p< 0.05). In conclusion, this study shows that soccer players face no significant difference between both groups during preseason, but significant difference in biomarkers of physiologic strain and hormonal stress-related parameters during the season suggest a positive balance in non-starters players.